2018
DOI: 10.1088/1367-2630/aab7cd
|View full text |Cite
|
Sign up to set email alerts
|

Coherence properties of the 0-πqubit

Abstract: Superconducting circuits rank among some of the most interesting architectures for the implementation of quantum information processing devices. The recently proposed 0-π qubit (Brooks et al 2013 Phys. Rev. A 87 52306) promises increased protection from spontaneous relaxation and dephasing. In this paper we present a detailed theoretical study of the coherence properties of the 0-π device, investigate relevant decoherence channels, and show estimates for achievable coherence times in multiple parameter regimes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 46 publications
2
143
0
Order By: Relevance
“…any low-degree polynomials in {f, θ, q f , q θ }. Equations (6), (7) lead together to the remarkably long coherence times expected for the qubit in the deep 0-π regime, as recently confirmed quantitatively in [22]. (a) Effective one-dimensional potential (black) and wave functions for the two lowest lying energy states (color), extracted using a Born-Oppenheimer approach (see appendix B).…”
Section: Qualitative Explanation Of Robustness To Noisesupporting
confidence: 55%
See 4 more Smart Citations
“…any low-degree polynomials in {f, θ, q f , q θ }. Equations (6), (7) lead together to the remarkably long coherence times expected for the qubit in the deep 0-π regime, as recently confirmed quantitatively in [22]. (a) Effective one-dimensional potential (black) and wave functions for the two lowest lying energy states (color), extracted using a Born-Oppenheimer approach (see appendix B).…”
Section: Qualitative Explanation Of Robustness To Noisesupporting
confidence: 55%
“…Using this approach, we predict coherence time enhancements between one and three orders of magnitude, depending on parameter regime. ζ-mode) [22]. Nevertheless, we found that the 0-π qubit still has the potential to outperform state-of-the-art superconducting devices.…”
mentioning
confidence: 79%
See 3 more Smart Citations